How do sulfamethoxazole and tetracycline affect the utilization of short chain fatty acids under anaerobic conditions?. Issue 1 (February 2018) - Cetecioglu, Z.; Orhon, D.
Graphical abstract: Abstract: The study focused on acute inhibition mechanism and effect of sulfamethoxazole (SMX) and tetracycline (TET) on the carboxylic acid utilization and the methanogenic activity. Duplicate batch reactors were operated in a range of 1–1000 mg/L for each antibiotic. Short chain fatty acid removal was determined in terms of soluble Chemical Oxygen Demand (COD) and specific fatty acid measurements together with methane generation. Additionally, seed sludge was characterized by Fluorescent in situ Hybridization (FISH). The inhibitory impacts of two antibiotics were variable with the initial dose. While in the lower sulfamethoxazole dosage, inhibition was observed in methanogenesis step. 35.8% and 46.8% inhibition in methane production were observed at 25 mg/L and 50 mg/L of SMX amended reactors. In higher SMX doses, short chain fatty acid utilization was inhibited even no acetate produced in the system. Inhibitory effect of tetracycline started at lower dose. 25% inhibition in methane production started at 1 mg/L of TET concentration. Additionally, it affected utilization of butyrate, propionate and acetate together. Tetracycline inhibited total microbial metabolism in terms of substrate utilization and methane generation between 500 mg/L and 1000 mg/L. FISH results showed that the dominant methanogenic group in the sludge was acetoclastic methanogens in term of Methanosarcina and Methanosaeta spp.